Employment dynamics and outsourcing in Celaya, Mexico: an analysis by economic sector - del Castillo Romo, Ruth; López-Mateo, Celina; Cañizarez-Espada, Manuela (RAN - Revista Academia & Negocios, 2020)
Productivity and competitivity of the enterprises in a region have a close relationship with labour market since public policies get to influence the different agents of the economy. The aim of this paper is to analyze the employment dynamics in the region of Celaya, Guanajuato, Mexico in the period of 2003-2013 by economic sector. We used a mixed method, applying the Regional Analysis Techniques for the quantitative approach, and semi-structured interviews for the qualitative approach. The interviews were applied to human resources managers. In that way, to get a full vision of the labour market dynamics in the city. Results show a growth on the number of employees hiring by the modality of subcontracting, and the relevance that the payment settlements have into manufacturing industry over the other sectors. This fact can imply that the manufacturing industry requires lower specialization levels. We conclude that labour flexibility has motivated the increase of outsourcing in different sectors and that it is related with an increase in salaries, which could mean a lack and/or oversupply of specialization in Celaya, Guanajuato, México.